A novel integrated system of three-dimensional electrochemical reactors (3DERs) and three-dimensional biofilm electrode reactors (3DBERs) for coking wastewater treatment. (July 2019) - Wu, Zhen-yu; Liu, Yang; Wang, Si-yuan; Peng, Pin; Li, Xiu-yan; Xu, Juan; Li, Wei-hua
Graphical abstract: Highlights: An integrated 3DERs-3DBERs system was applied in coking wastewater treatment. 3DERs contributed to COD and nitrogen removal through electrochemical reactions. 3DBERs were responsible for nitrification process by enriching functional microbes. 79.63% of COD and 76.30% of TN was eliminated at energy consumption of 15.6 kWh/m 3 . Abstract: Treatment of coking wastewater is a great challenge due to their instinct characteristics of high concentration, complex composition and biological toxicity. In this work, a novel integrated system comprising three-dimensional electrochemical reactors (3DERs) and three-dimensional biofilm electrode reactors (3DBERs) in series is developed for coking wastewater treatment. Results indicate that 79.63% of COD as well as 76.30% of total nitrogen could be removed at the low energy consumption of 15.6 kWh/m 3 . 3DERs mainly contribute to COD and nitrogen removal through electrochemical oxidation/reduction, while 3DBERs are responsible for nitrification process by enriched functional microbes. After treating by the integrated system, only long-chain alkanes are left in the wastewater and the toxicity of effluent is significantly reduced. This integrated 3DERs-3DBERs system exhibits capability of simultaneously eliminating carbonaceous and nitrogenous contaminants in coking wastewater, and greatly saves the energy with synergy of electricity and biofilm.